KEPUASAN KERJA SEBAGAI PENDORONG KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Rojuaniah, Rojuaniah (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
This study examined the effect of job satisfaction on organizational citizenship behavior (OCB) either directly or through organizational commitment. The purpose of this study is to analyze whether job satisfaction can influence OCB through organizational commitment. Objects and respondents in this research are private university lecturers in West Jakarta area. Data collection by using questioner and direct interview with selected respondents. Research design is causality with data processing method using path analysis. The results shows job satisfaction influences organizational commitment and organizational citizenship behavior (OCB) of lecturers, while organizational commitment directly affects organizational citizenship behavior (OCB). The direct effect of job satisfaction on organizational citizenship behavior (OCB) is greater than the effect of job satisfaction on organizational citizenship behavior (OCB) through organizational commitment. This indicates that a lecturer will still have a greater dedication to his work or profession and remain responsible and caring for his organization even if there is no fixed linkage to the organization where he works. Keywords: job satisfaction, organizational commitment, organizational citizenship behavior (OCB)